Competition and Efficiency of Takaful and Conventional Insurance Markets in Gulf Cooperation Council (GCC) Countries - Asif, Ahmed (Universiti Malaysia Sarawak (UNIMAS), 2021)
Conventional has been in existence for many centuries so it is deeply rooted thus it benefits from operational experience it has been through whereas Takaful is of a recent origin with facing issues related to efficiency performance. Thus, the objective of this study is to analyse degree of competition, efficiency performance and finally the relationship between efficiency and competition for Takaful and conventional in Gulf Cooperation Council (GCC) countries for the period 2015 to 2019 by using an unbalanced set of 140 Takaful and conventional companies. Lerner index employed for measure market power represents degree of competition level and Data Envelopment Analysis (DEA) were used to estimate the efficiency level. Granger test employed to examine the causality between efficiency and competition. The empirical results show that Takaful firms are equally efficient compared to conventional firms. The Takaful when compared to conventional is highly technical and pure technical efficient however it’s moderately cost efficient and there is a large opportunity for improvement. In nutshell, Technical Efficiency correlated with Lerner Index and Lerner Index associated with Allocative Efficiency in long run for Takaful firms while conventional firms Lerner Index related with Allocative Efficiency and Scale Efficiency in long run.